Census, characteristics, and taxonomy of urban health indicator tools: a systematic review. (November 2017) - Pineo, Helen; Glonti, Ketevan; Rutter, Harry; Zimmermann, Nici; Wilkinson, Paul; Davies, Michael
Abstract: Background: Urban health indicator (UHI) tools offer one form of evidence about the urban environment's impact on health to inform built environment policy and decision making, particularly in relation to health and spatial inequalities. Many UHI tools have been developed, potentially duplicating scarce resources, with little knowledge of their subsequent impact on policy. This study aimed to examine the nature and characteristics of UHI tools to increase understanding of their potential use by municipal built environment policy and decision-makers. Methods: The methods of this systematic review are detailed in our published protocol, including a PRISMA-P checklist. We defined UHI tools as compilations of UHIs that needed to measure at least two physical urban environment characteristics. We searched seven bibliographic databases, four key journals, and six practitioner websites, and conducted Google searches between Jan 27, 2016, and Feb 24, 2016, for UHI tools. We extracted data from primary studies and online indicator systems. Findings: We included 198 documents, which identified 145 UHI tools comprising 8006 indicators, from which we developed a taxonomy of indicators (using a hybrid inductive and deductive approach). The diversity in UHI tools was extensive with respect to topic, spatial scale, format, scope, and purpose, which we identified as key taxonomic classifiers. Over time, the proportion of UHI tools that measured data at the neighbourhood and lower scale increased, as did the proportion of tools that presented data via interactive maps. This increase reflected growing analytical capability, and offered the potential for improved understanding of the complexity of influences on urban health (an aspect noted as being especially challenging by some indicator producers). Interpretation: UHI tools of increasing sophistication provide insights into multiple dimensions of the urban environment and their impacts on health, but they are not always used in the policy and decision-making process. In addition, many indicators have only an indirect association with health impacts attributable to modifiable urban environment characteristics. Further research is needed to understand the form and presentation of indicators that are of greatest utility to built environment policy development, and that reflect community input and health and development priorities. Funding: HP is fully funded by the Building Research Establishment Ltd. HR was supported by the National Institute for Health Research Collaboration for Leadership in Applied Health Research and Care North Thames at Barts Health NHS Trust.